2009
DOI: 10.1590/s0004-28032009000400009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of familial adenomatous polyposis: ileoretal anastomosis or restorative proctolectomy?

Abstract: -Context -Controversy regarding the best operative choice for familial adenomatous polyposis lays between the morbidity of restorative proctocolectomy and the supposed mortality due to rectal cancer after ileorectal anastomosis. Objectives -To evaluate operative complications and oncological outcome after ileorectal anastomosis and restorative proctocolectomy. Among the 26 patients followed after restorative proctocolectomy, it was found cancer in the ileal pouch in 1 (3.8%). Conclusions -1. Operative complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…With the increasing incidence of Clostridium difficile colitis and the emergence of more virulent strains [4], subtotal colectomy has become a more common emergent procedure with a mortality rate ranging from 30% to 80% [4]. While we were unable to identify diagnosis as an independent predictor of mortality, it can be assumed from previous studies that subtotal or total colectomy for familial adenomatous polyposis or ulcerative colitis with dysplasia has a much lower 30-d mortality rate than it does in patients with a fulminant infectious colitis or toxic megacolon [4,17,38,39]. Thus, it may be more appropriate to look at subtotal colectomy as predictor of mortality in urgent or emergent cases rather than elective procedures.…”
Section: Risk Factors For Mortality After Colectomymentioning
confidence: 84%
“…With the increasing incidence of Clostridium difficile colitis and the emergence of more virulent strains [4], subtotal colectomy has become a more common emergent procedure with a mortality rate ranging from 30% to 80% [4]. While we were unable to identify diagnosis as an independent predictor of mortality, it can be assumed from previous studies that subtotal or total colectomy for familial adenomatous polyposis or ulcerative colitis with dysplasia has a much lower 30-d mortality rate than it does in patients with a fulminant infectious colitis or toxic megacolon [4,17,38,39]. Thus, it may be more appropriate to look at subtotal colectomy as predictor of mortality in urgent or emergent cases rather than elective procedures.…”
Section: Risk Factors For Mortality After Colectomymentioning
confidence: 84%
“…Long-term follow-up after IRA revealed that 24–43% of patients develop cancer in the remaining rectum [ 116 , 117 ]. During a 20-year period after IRA, the rectum had to be resected in 10% of patients with AFAP, 39% of patients with sparse FAP, and 61% of patients with severe FAP [ 118 ].…”
Section: Commentsmentioning
confidence: 99%
“…Long-term follow-up after IRA has revealed that 24-43% of patients develop cancer in the remaining rectum 75,76) . During a 20-year period after IRA, the rectum had to be resected in 10% of patients with AFAP, 39% of patients with sparse FAP, and 61% of patients with profuse FAP 37) .…”
Section: Cq9: How Should the Risk Of Rectal Cancer Development Be Manmentioning
confidence: 99%